(untitled) (Training and Practice : Journal of Educational Sciences, 2013)
The launch of the Hungarian National Core Curriculum (NCC) in 1998 resulted in combat sports and self-defence becoming a part of the cultural domain ‘Physical Education and Sport’. This article focuses on the historical preliminaries and highlights the process of introducing combat sports into education. Moreover, it addresses issues relating to considerable pedagogic possibilities and alternatives behind school martial arts education while emphasizing the possible difficulties as well. An additional aim is to serve an example for foreign authors of teaching physical education in Hungary. Furthermore, the authors intend to acknowledge the work and scientific achievements of Dr. Ferenc Galla – the associate professor and chairman of the Combat Sports Department of the former Hungarian College of Physical Education (TF).